Keutamaan Manusia Hindu dalam Pandangan Sārasamuccaya - Putu Dana Yasa; I Putu Sumartana (Sphatika: Jurnal Teologi, 2022)
Humans in this life have a more noble position compared to other living beings, the reason is none other than because humans have thoughts. This mind is a source of human strength and weakness in understanding the nature and virtue of being born as a human. To be able to understand what Hindu humans should do in life, the Sārasamuccaya scriptures provide benevolent teachings which explain that in this life every human being must prioritize good actions or behavior. Doing good is one way to be able to escape from all worldly attachments as well as a way to unite with God. The purpose of writing this article is to provide understanding for Hindus to always be guided by the sacred Vedic literatures in this case is Sārasmuccaya. This study is a qualitative study using a theological approach regarding the nature and virtue of Hinduism in the sacred literature of Sārasamuccaya. In the Sārasamuccaya it is clearly stated that the simple virtue of man in this life is being able to do good.